2021
DOI: 10.34172/jrhs.2021.67
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Coronavirus Disease 2019 Outbreak on Children and Adolescents with Type 1 Diabetes Mellitus

Abstract: Background: This study aimed to investigate the impact of the Coronavirus Disease 2019 (COVID-19) pandemic on daily routines and health of patients with type 1 diabetes mellitus (T1DM). Study design: A cross-sectional study. Methods: This study included 98 children and adolescents with type 1 diabetes who were regularly followed up in the Endocrinology outpatient clinic of Besat Hospital, Hamadan, Iran, in 2020. The primary measurements included body mass index, glycemic control, number of hypoglycemic events,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…We found 33 studies that looked at the effects of COVID-19 on diabetes among children/adolescents ( Table 1 [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24*] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38*] , [39] , [40] , [41] , [42] , [43] , [44] , [45*] , [46] , [47*] ), of which most focused only on those with TID. One study included both T1D and T2D [46] and one T2D [47] ( Table 1 ).…”
Section: Condition Specific Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found 33 studies that looked at the effects of COVID-19 on diabetes among children/adolescents ( Table 1 [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24*] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38*] , [39] , [40] , [41] , [42] , [43] , [44] , [45*] , [46] , [47*] ), of which most focused only on those with TID. One study included both T1D and T2D [46] and one T2D [47] ( Table 1 ).…”
Section: Condition Specific Findings and Discussionmentioning
confidence: 99%
“…Stipulated reasons for above observations include potential diabetogenic action of the virus itself, as well as behavioural factors such as avoidance of hospital visits, and logistic factors such as overload of the healthcare system during the pandemic [24*] , [26] , [27] , [34] , [51] , [52] . Three studies highlighted that the incidence of hypoglycaemic events as well as hospitalization with hypoglycaemia were low during the lockdown period [19] , [30] , [44] , and one of those studies reported that this reversed after lifting of the lockdown [44] .…”
Section: Condition Specific Findings and Discussionmentioning
confidence: 99%
“…DMFT/dmft has been used to determine oral health in children and adults with type 1 diabetes mellitus (Rafatjou et al, 2016), HIV‐positive adults, and children receiving antineoplastic treatment (Wang et al, 2020), as well as in various conditions, such as fetal alcohol syndrome (Blanck‐Lubarsch et al, 2019), ALL, and ALL/AML (Dubey et al, 2018), orthodontic anomalies (Kukletova et al, 2012), and prosthodontic problems (Zhang et al, 2007). It has also been evaluated according to the presence of a short dental arch (Zhang et al, 2007), high sugar intake (Hong et al, 2018), and tooth brushing habits (Gibson & Williams, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study involving 98 children and adolescents with T1D identified several key challenges faced by Iranian patients due to pandemic restrictions. These challenges included the necessity for increased insulin doses, reduced physical activity, insulin shortages, and missed morning insulin doses [ 30 ]. Other studies also noted weight gain, a significant rise in HbA1c levels, and an increase in daily insulin requirements among children with T1D during the pandemic [ 31 , 32 ].…”
Section: Epidemiologymentioning
confidence: 99%